Geometrically frustrated Fe2P-like systems: beyond the Fe-trimer approximation. (30th June 2015) - Florez, J M; Negrete, O A; Vargas, P; Ross, C A
Abstract: Fe P-like structures can be strongly frustrated magnets due to their Kagome/triangular intercalated-layer structure. A complete magnetic solution of the complex spin architecture, and hence the full potential of the magnetic phenomena in Fe P-like material prototypes, is yet to be found. A previous magnetic model for a representative FeCrAs-like system used a mean-field effective-spin to describe the 3g-Wyckoff located Fe-triangles. Such an approach demonstrated the outstanding magnetocaloric properties of the material but left the question of whether the intra-trimer interaction could lead to new physical phenomena and therefore more potentially useful properties. In this work Monte Carlo simulations are employed in order to understand both the influence of the additional degrees of freedom introduced by the Fe-trimers and the changes caused by all the possible exchange couplings between them. Complex scenarios arise, in which FM coupling in the trimers gives rise to both in-plane and out-of-plane inter-layer AFM states; whereas AFM exchange in the trimers gives rise to three distinct states, i.e. AFM-canted layers, a non-collinear superposition of ferromagnetic Kagome/triangular orderings, and tilted inter-planar AFM order. These last three configurations generate a double bifurcated magnetic phase diagram while the first one mimics the behavior seen in a model that treats the trimer as an effective-spin under an applied magnetic field.